Tantangan Investasi dan Teknologi dalam Transformasi Kawasan Industri Tradisional Menuju Eco-Smart - Syafrijon; Hardjomuljadi, Sarwono; Anondho, Basuki (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2025)
The transformation of traditional industrial areas into eco-smart zones has become a strategic solution for reducing environmental impacts while improving operational efficiency. This study aims to analyze investment and technology challenges in the transformation of traditional industrial estates towards eco-smart industrial estates, as well as evaluate their impact on the company's environmental, economic, and social sustainability. The research employs a mixed-methods approach, integrating quantitative data analysis from the implementation of eco-smart technology across various industrial sectors with interviews involving key stakeholders. Quantitative data includes CO2 emission reductions, operational cost efficiencies, and natural resource management, while interviews explore the challenges and opportunities in technology adoption. The findings reveal that implementing eco-smart technology over four years successfully reduced CO2 emissions by 50%, achieved 40% energy cost efficiency, and generated a total operational cost saving of 26%. Additionally, the use of natural resources, such as water and energy, decreased by 20%. The main challenges identified include high initial investment and the need for collaboration among stakeholders to accelerate technology adoption. This study concludes that despite the hurdles in investment and technology implementation, transitioning to eco-smart systems offers significant environmental and economic benefits. These findings provide valuable insights for policymakers and industry players in developing sustainable industrial zones.